Douglas Kellner e os estudos de mídia : exame crítico das ideias de um teórico Norte-Americano - Daros, Otavio (2018)
Douglas Kellner (✡1943) emerged in the 1990's as a leading scholar of media phenomena. This research seeks to reconstruct his trajectory in this area of knowledge. His ideas are analyzed by assessing their merits and problems, progress and difficulties. It is emphasized the way in which his intellectual course was influenced by the so-called western marxism, in particular by the School of Frankfurt. It also highlights how the author approaches cultural studies by appropriating the legacy of the Center for Contemporary Cultural Studies. Kellner makes both currents dialogue, in the shadow of discussions about postmodernism and the so-called cultural wars in the United States. Aiming to show how all this has repercussions in his analysis of what he called “media culture”, and then “era of the spectacle”, first his ideas are contextualized historically and intellectually. Second, his proposal for media literacy is analyzed, as a pragmatic dimension of his critical study of the media. Subsequently, the application of his studies about cinema and, especially, television is evaluated. In the end, the material presented is commented, interpreted, and criticized, making the study of media theories dialog with other areas of knowledge. In conclusion, Kellner proposes an innovative synthesis in theoretical and methodological terms, profiled with the so-called cultural Marxism. But also that it is not exempt of conceptual contradictions that generate analytical simplifications during the research, apparently deriving from unbridled ideological commitments.